2019
DOI: 10.1249/mss.0000000000001901
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Sedentary Time: Association with Metabolic Health and Liver Fat

Abstract: Introduction/Purpose To investigate whether (a) lower levels of daily physical activity (PA) and greater sedentary time accounted for contrasting metabolic phenotypes (higher liver fat/presence of metabolic syndrome [METS+] vs lower liver fat/absence of metabolic syndrome [METS−]) in individuals of similar body mass index and (b) the association of sedentary time on metabolic health and liver fat. Methods Ninety-eight habitually active participants (53 female, 45 male; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…In the second study [28], IL-6 was also increased and after returning to normal activity, inflammatory markers were still elevated. In contrast, in the studies conducted in young individuals, no changes were produced in inflammatory parameters [20,22,25,26].…”
Section: Detrimental Health Effects Of An Acute Sedentary Lifestyle Imentioning
confidence: 75%
See 2 more Smart Citations
“…In the second study [28], IL-6 was also increased and after returning to normal activity, inflammatory markers were still elevated. In contrast, in the studies conducted in young individuals, no changes were produced in inflammatory parameters [20,22,25,26].…”
Section: Detrimental Health Effects Of An Acute Sedentary Lifestyle Imentioning
confidence: 75%
“…Other authors have looked at what happens when a reduction in physical activity and overfeeding are accompanied by an exercise intervention [26]. Over one week, 26 physically active men (25 (7) years; BMI 23.8 (2.5)) were randomly assigned to two groups.…”
Section: Metabolic Effects Of Acute Physical Inactivity Plus Overfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, leisure time activities of teachers may be more susceptible to sedentary choices, as television viewing, computer and cellphone use, and consequently be significantly affected by sedentary breaks at this domain. Another factor is that sedentary behavior has been associated with unhealthy metabolic health, regardless of physical activity levels 39) and high sedentary breaks at leisure may be able to mitigate the health impairments of sedentary behavior by reducing its accumulation in longer periods and by decreasing the sedentary time overall. Healy et al…”
Section: Discussionmentioning
confidence: 99%
“…18,20 A study was conducted in the UK to investigate the effect of physical activity and sedentary time on metabolic health and liver adiposity. 21 Results revealed that greater time spent in sedentary was associated with MetS, independent of physical activity levels. More recently, cross-sectional data suggested that high level of sedentary time was associated with poorer glycemic control in people with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 89%